Disiloxane with nitrile end groups as Co-solvent for electrolytes in lithiumsulfur batteries – A feasible approach to replace LiNO3. (1st June 2019) - Mukra, Tzach; Horowitz, Yonatan; Shekhtman, Inna; Goor, Meital; Drvarič Talian, Sara; Burstein, Larisa; Kasnatscheew, Johannes; Meister, Paul; Grünebaum, Mariano; Winter, Martin; Wiemhöfer, Hans-Dieter; Golodnitsky, Diana; et al.
Abstract: The lithium-sulfur battery is a leading candidate for a new-generation Li-ion battery, because of its high theoretical capacity and abundance of sulfur. Yet, the flammability of either the organic-carbonate or ether-based electrolytes used in such battery systems is of concern. Moreover, the oxidation of Li2 S leads to the formation of polysulfides (Li2 S3-8 ), which dissolve in the electrolyte and initiate a shuttle mechanism, which results in low Coulombic efficiency and growth of a thick SEI on the anode. Therefore, various electrolyte additives, like LiNO3, are added to the electrolyte. Unfortunately, the nitrate additive is gradually consumed and the "shuttle effect" resumes. Here we present a LiNO3 -free electrolyte consisting of nitrile-functionalized disiloxane (TmdSx-CN) with dissolved LiTFSI as a candidate electrolyte for lithium-sulfur batteries. We have examined the effect of TmdSx-CN as a co-solvent along with 1, 3-dioxolane (DOL) on the performance of Li/S cells. It was found that LiNO3 -free TmdSx-CN:DOL electrolyte mitigates the polysulfide shuttle. The cell containing this electrolyte yields an average capacity of 700 mAh g −1 and 96% Coulombic efficiency for more than 100 cycles. Moreover, 87.5% energy efficiency, which is similar to the LiNO3 -based control cell. We expect that our preliminary results will encourage the further use of siloxane-based electrolytes in metallic-lithium battery systems, and specifically, in lithium-sulfur batteries.